2016
DOI: 10.1080/13691058.2016.1217565
|View full text |Cite
|
Sign up to set email alerts
|

Risky Business: condom failures as experienced by female sex workers in Mombasa, Kenya

Abstract: Limited research exists about condom failure as experienced by female sex workers. We conducted a qualitative study to examine how female sex workers in Mombasa, Kenya contextualise and explain the occurrence of condom failure. In-depth, semi-structured interviews were conducted with thirty female sex workers to ascertain their condom failure experiences. We qualitatively analysed interview transcripts to determine how the women mitigate risk and cope with condom failure. Condom failure was not uncommon, but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Having sex in a position where FSWs cannot control the actions of the client also opens the door for condom failure. Therefore, programs need to make a special effort to identify FSWs who appear to be more susceptible to breakage/slippage and provide information and skills to minimize their risk for HIV/STI infection [ 13 , 20 ]. Although they work under difficult conditions, FSWs try to maintain their safety by controlling the condom use process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having sex in a position where FSWs cannot control the actions of the client also opens the door for condom failure. Therefore, programs need to make a special effort to identify FSWs who appear to be more susceptible to breakage/slippage and provide information and skills to minimize their risk for HIV/STI infection [ 13 , 20 ]. Although they work under difficult conditions, FSWs try to maintain their safety by controlling the condom use process.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among FSWs in China ( N = 200) and South Africa ( N = 100) also found that poor condom fit, the duration and roughness of the sex act, and the use of drugs and alcohol contributed to condom breakage/slippage [ 11 , 12 ]. To minimize the incidence of condom failure, interventions including learning about proper condom use and applying condoms oneself, have been recommended [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was a major misconception among the blood donors who thought that common preventive measures can completely prevent them from contracting sexually transmissible infections (STIs). Previous studies have found that oral sex may cause STIs while condom failure is not uncommon (28, 29). Accordingly, awareness regarding STIs should be enhanced to ensure transfusion blood safety.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies evaluating factors associated with condom failures in African settings were comparatively small 23 and were often conducted in the context of female sex work 24 that is associated with power imbalances, deliberate condom damage by male clients, 25 and not exclusively focused on anal sex. 23 Others are almost a decade old. 26 Studies focusing on condom failure in African MSM likewise tend to be small, cross sectional, focused on sex workers and their clients, and do not include TGW.…”
Section: Introductionmentioning
confidence: 99%